Homozygous germ-line mutation of the PMS2 mismatch repair gene: a unique case report of constitutional mismatch repair deficiency (CMMRD) - N. C. Ramchander; N. A. J. Ryan; E. J. Crosbie; D. G. Evans (BMC, 2017)
Abstract Background Constitutional mismatch repair deficiency syndrome results from bi-allelic inheritance of mutations affecting the key DNA mismatch repair genes: MLH1, MSH2, MSH6 or PMS2. Individuals with bi-allelic mutations have a dysfunctional mismatch repair system from birth; as a result, constitutional mismatch repair deficiency syndrome is characterised by early onset malignancies. Fewer than 150 cases have been reported in the literature over the past 20 years. This is the first report of the founder PMS2 mutation - NM_000535.5:c.1500del (p.Val501TrpfsTer94) in exon 11 and its associated cancers in this family. Case presentation The proband is 30 years old and is alive today. She is of Pakistani ethnic origin and a product of consanguinity. She initially presented aged 24 with painless bleeding per-rectum from colorectal polyps and was referred to clinical genetics. Clinical examination revealed two café-au-lait lesions, lichen planus, and a dermoid cyst. Her sister had been diagnosed in childhood with an aggressive brain tumour followed by colorectal cancer. During follow up, the proband developed 37 colorectal adenomatous polyps, synchronous ovarian and endometrial adenocarcinomas, and ultimately a metachronous gastric adenocarcinoma. DNA sequencing of peripheral lymphocytes revealed a bi-allelic inheritance of the PMS2 mutation NM_000535.5:c.1500del (p.Val501TrpfsTer94) in exon 11. Ovarian tumour tissue demonstrated low microsatellite instability. To date, she has had a total abdominal hysterectomy, bilateral salpingo-oophorectomy, and a total gastrectomy. Aspirin and oestrogen-only hormone replacement therapy provide some chemoprophylaxis and manage postmenopausal symptoms, respectively. An 18-monthly colonoscopy surveillance programme has led to the excision of three high-grade dysplastic colorectal tubular adenomatous polyps. The proband's family pedigree displays multiple relatives with cancers including a likely case of 'true' Turcot syndrome. Conclusions Constitutional mismatch repair deficiency syndrome should be considered in patients who present with early onset cancer, a strong family history of cancer, and cutaneous features resembling neurofibromatosis type I. Immunohistochemistry analysis of tumour and normal tissue is sensitive and specific for identifying patients with mismatch repair deficiency and should direct DNA sequencing of lymphocytic tissue to establish a diagnosis. Microsatellite instability status appears to be of little value in identifying patients who may have constitutional mismatch repair deficiency syndrome.